Financial Challenges Faced by the Elderly in the Context of Population Growth: A Critical Analysis of Pakistani Family Dynamics (Journal of Asian Development Studies, 2025)
The research explores financial challenges experienced by senior citizens across Punjab, Pakistan, while studying different family types like nuclear, extended, and joint families. The research gathered data from 1,000 elderly participants throughout six cities through a stratified proportional sampling approach. The study results demonstrate that joint-family households achieve slightly better financial stability and income than nuclear families and extended families through their mean income score of 3.12. According to demographic information, 21.6% of participants belong to the 80+ age group, and 35.3% selected the category "other" when asked about gender. Secondary education represents 17.2% of respondents, while 16.5% did not complete formal schooling. The income analysis demonstrates that 20.5% of respondents have a monthly income below 10,000 PKR, and 23% earn between 20,000 and 29,000 PKR monthly. Financial well-being indicators between family types demonstrate no substantial variations except for income (F = 2.9993, p = 0.050) and living arrangements (F = 2.7699, p = 0.063), which have marginal significance. The research demonstrates that financial instability affects older adults at high rates regardless of their family relationships. The study argues that Punjab requires policy reforms that combine better social security with affordable healthcare and community-based support programs to help protect vulnerable elderly citizens.